Potential of Aspergillus flavus Secondary Metabolites in Breast Cancer Treatment In-silico study of fungal compounds targeting tumor suppressor proteins - Alsharif, Shahad S.; Sajer , Bayan H. (Journal of Contemporary Medical Sciences, 2025)
Objectives: Breast cancer is one of the leading causes of mortality worldwide, with existing treatments often accompanied by significant side effects. This study aimed to explore the therapeutic potential of secondary metabolites derived from Aspergillus flavus in targeting key tumor suppressor proteins associated with breast cancer, namely BRCA1, BRCA2, and TP53. Methods: An in-silico approach was employed to screen and evaluate fungal secondary metabolites. Molecular docking studies were conducted to assess the binding affinity of these compounds to BRCA1, BRCA2, and TP53 proteins. In addition, the pharmacological profiles of the compounds were analyzed, including ADME (absorption, distribution, metabolism, and excretion), cytotoxicity on cancer cell lines, and cardiotoxicity predictions. Results: Among the analyzed secondary metabolites, vitexin demonstrated the highest binding affinity to BRCA1, BRCA2, and TP53, suggesting a strong potential for inhibiting these tumor suppressor proteins. The compound also showed favorable pharmacokinetic and safety profiles, indicating its suitability as a drug candidate. Conclusion: Vitexin from Aspergillus flavus shows promise as a lead compound for the development of selective and effective inhibitors targeting tumor suppressor proteins involved in breast cancer. This study provides a foundational step toward designing safer and more targeted therapeutics using fungal-derived bioactive compounds.